Patriarchy in Text and Context: A Synthesis of Paul Ricoeur’s Hermeneutics and Mansour Fakih’s Structural Analysis - Ningrum, Dian Astria Puspa; Subangga, Bymmas; Mahzumi, Fikri (Journal of Islamic Thought and Philosophy, 2025)
This study explores Islamic feminism, a movement that reinterprets Islamic teachings by emphasizing justice and gender equality. Rooted within the Islamic tradition, Islamic feminism asserts that authentic Islamic values uphold, rather than marginalize, women's dignity. The research examines Islamic feminism both theoretically and contextually, showing how religious texts can function as tools of liberation or oppression. Using Paul Ricoeur's critical hermeneutics and Mansour Fakih's structural analysis, the study reveals that Islamic feminism extends beyond theological debates—it also challenges patriarchal structures embedded in social, cultural, and political life. By uncovering these dynamics, the research emphasizes Islamic feminism's potential to foster critical gender awareness and promote more inclusive, just, and contextually relevant religious practices. This approach not only affirms women's rights within Islam but also repositions the faith as a source of empowerment and transformative change.